Ecological and Legal Analysis of Anoa (Bubalus spp.) Habitat Population: Endemic Species of Sulawesi in the Context of Mining Activities - Muhammad Sabaruddin Sinapoy; Basrin Melamba (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Mining constitutes a strategic sector for national economic growth in Indonesia; however, it simultaneously exerts significant ecological pressure on biodiversity, particularly on the endemic species of Sulawesi Island. The Anoa (Bubalus depressicornis and Bubalus quarlesi) is an endangered endemic species that is critically dependent on tropical forest ecosystems. Sulawesi functions not only as a major centre of mining expansion but also as a core biodiversity hotspot within the Wallacea region. Method: This study applies a normative-empirical legal method integrating statutory and conceptual approaches with ecological analysis, conservation literature, and government reports covering the 2015–2023 period. Result: Mining expansion particularly nickel mining in Central and Southeast Sulawesi—has resulted in primary and secondary forest cover loss, fragmentation of ecological corridors, declining water quality, and increased human access to Anoa habitats. Regulatory disharmony among forestry, conservation, and mining laws permits mining licenses through forest-borrowing schemes, thereby weakening species protection. Research Limitations: The study is limited by the absence of systematic population monitoring data post-2019 and reliance on secondary ecological datasets. Conclusion: The findings call for ecosystem-based licensing reform to prevent local extinction and ensure the sustainability of Sulawesi's biodiversity. This study is among the first to construct a multi-layered causal pathway model linking mining-induced deforestation to endemic ungulate population decline within an integrated ecological-legal framework in Indonesia. Keywords: Mining; Habitat Degradation; Endemic Species; Anoa; Sulawesi; Conservation; Biodiversity Law